CXCR1 and CXCR2 Inhibition by Ladarixin Improves Neutrophil-Dependent Airway Inflammation in Mice - Mattos, Matheus Silverio; Ferrero, Maximiliano Ruben; Kraemer, Lucas; Lopes, Gabriel Augusto Oliveira; Reis, Diego Carlos; Cassali, Geovanni Dantas; Oliveira, Fabricio Marcus Silva; Brandolini, Laura; Allegretti, Marcello; Garcia, Cristiana Couto; Martins, Marco Aurélio; Teixeira, Mauro Martins; et al. (Frontiers in Immunology, 2020)
RATIONALE: Increased IL-8 levels and neutrophil accumulation in the airways are common features found in patients affected by pulmonary diseases such as Asthma, Idiopathic Pulmonary Fibrosis, Influenza-A infection and COPD. Chronic neutrophilic inflammation is usually corticosteroid insensitive and may be relevant in the progression of those diseases. OBJECTIVE: To explore the role of Ladarixin, a dual CXCR1/2 antagonist, in several mouse models of airway inflammation with a significant neutrophilic component. FINDINGS: Ladarixin was able to reduce the acute and chronic neutrophilic influx, also attenuating the Th2 eosinophil-dominated airway inflammation, tissue remodeling and airway hyperresponsiveness. Correspondingly, Ladarixin decreased bleomycin-induced neutrophilic inflammation and collagen deposition, as well as attenuated the corticosteroid resistant Th17 neutrophil-dominated airway inflammation and hyperresponsiveness, restoring corticosteroid sensitivity. Finally, Ladarixin reduced neutrophilic airway inflammation during cigarette smoke-induced corticosteroid resistant exacerbation of Influenza-A infection, improving lung function and mice survival. CONCLUSION: CXCR1/2 antagonist Ladarixin offers a new strategy for therapeutic treatment of acute and chronic neutrophilic airway inflammation, even in the context of corticosteroid-insensitivity.